Penetapan Nilai Paten Lembaga Litbang pemerintah - Syahrul Aiman (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2014)
Patent as Intellectual Property Right (HKI) is the result of research and development (R&D) activity, vital to boost industry development and plays an important role in increasing business competitiveness of a country. Based on Government Regulation No. 6 Year 2006, HKI of public R&D institution as a result of R&D financed by government is public asset; therefore, it must be protected and valuated. The patent containing technology invention is under legal protection and can be commercialized; therefore, its value is affected by factors of technology, law and commercial aspect. The numerous factors influencing patent value makes patent valuation hard to conduct, so there emerge various researches and studies, proposing various methods to determine patent value. Although patent value as public asset must be determined, there has not been any way or method of patent valuation, set or agreed on; thus many R&D institutions encounter trouble in determining the value of a patent. This paper studies various methods published, and recommends Compensation Method as appropriate for patent valuation as a state asset, since this method calculates various fundamental matters affecting patent value, namely the costs in the past and in the future, and potential income if the patent is used commercially. Besides, the calculation process in this method can be conducted quickly by using spreadsheet software commonly known.